The Impact of Peyton’s Four Stages Approach on Trauma Health Practitioners Competence and Practice - Momi Gul Khattak (18466425) (2024)
Background Trauma is a leading cause of death and traumatic injuries remain an important cause of high morbidity and mortality rates.1 A thorough patient assessment, application of rapid diagnostic tests, and early activation of resources are vital for ensuring optimal outcomes in patients with traumatic injuries.2 The American College of Surgeons (ACS) and the Society of Trauma Nurses (STN) have established Advanced Trauma courses. Hamad Medical Corporation (HMC) adopted and mandated these advanced trauma courses for doctors and nurses likely to be involved in trauma management and care to enhance confidence, competence, and trauma clinical practices. For mastery of trauma-related skills, full-scale scenario-based simulation using a patient simulator was used incorporating four stages of Peyton’s approach. 3 This approach consisted of the following four steps: demonstration, deconstruction, comprehension, and performance. 3 This describes the impact of simulation-based education using Peyton’s four stages approach on trauma?related perceived learners’ satisfaction, competence, and practices. Methods A self-reported questionnaire was obtained from trauma practitioners (N=160) who attended the trauma courses between January 2021 and August 2023 (Table 1). The questionnaire was collected as a post-course evaluation with a response rate of 100%. Descriptive analyses were performed using SPSS version 28. Results The full-scale scenario-based simulation using a patient simulator incorporating Peyton’s four stages approach positively impacted learners’ satisfaction, and perceived trauma skills competence and clinical practices (Table 2).